2003
DOI: 10.1007/s00439-002-0851-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel immunoglobulin superfamily gene cluster, mapping to a region of human chromosome 17q25, linked to psoriasis susceptibility

Abstract: Chromosome 17q25 harbors a susceptibility locus for psoriasis ( PSORS2). This locus may overlap with loci for atopic dermatitis and rheumatoid arthritis. To further refine the location of PSORS2, we genotyped 242 primarily nuclear families for 15 polymorphic microsatellites mapping to chromosome 17q23-q25. Non-parametric linkage analysis revealed a linkage peak lying close to a novel cluster of genes from the immunoglobulin (Ig) superfamily. This cluster spans >250 kb and harbors five CMRF35-like genes and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…This family is encoded in a region of human chromosome 17 (17q24-q25), and as in other inhibitory receptor families, the CMRF-35 cluster includes ITIM-bearing molecules as well as short-tailed proteins [16,17]. Members of this gene family have been shown to be expressed on cells of different hematopoietic lineages, such as T cell subsets, B lymphocytes, NK cells, monocytes, macrophages, and granulocytes [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This family is encoded in a region of human chromosome 17 (17q24-q25), and as in other inhibitory receptor families, the CMRF-35 cluster includes ITIM-bearing molecules as well as short-tailed proteins [16,17]. Members of this gene family have been shown to be expressed on cells of different hematopoietic lineages, such as T cell subsets, B lymphocytes, NK cells, monocytes, macrophages, and granulocytes [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that together with other inhibitory molecules, this receptor may contribute to keep a threshold of activation, counterbalancing the function of other triggering receptors of the same [16] or other families expressed on myeloid cells (i.e. FcR, TREM, ILT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD300a is a receptor with three ITIM motifs within its cytoplasmic tail that belongs to a multigene family of activating/inhibitory receptors that are clustered in human chromosome 17 (17q25.1) (Speckman et al, 2003). CD300a is expressed on a variety of immune cells (Cantoni et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the CD300a gene receptor ranks near the top of the human genes that show evidence of positive selection Nielsen et al, 2005), suggesting an important role for this receptor. Genetic studies have found that a nonsynonymous polymorphism within the immunoglobulin domain (R111Q) of the CD300a receptor is linked to psoriasis susceptibility (Speckman et al, 2003). Cross-linking of the CD300a receptor with a specific monoclonal antibody (mAb) has been shown to exert an inhibitory effect on natural killer (NK) cell activity through recruitment of src homology 2 domain (SH2)-containing tyrosine phosphatase (SHP)-1 and SHP-2 phosphatases (Cantoni et al, 1999).…”
Section: Introductionmentioning
confidence: 99%